Carnosine as a protective factor in diabetic nephropathy: association with a leucine repeat of the carnosinase gene CNDP1 - Janssen, Bart; Rose, Daniela; Brinkkötter, Paul-Thomas; Peters, Verena; Rind, Nina; Fischer, Christine; Rychlik, Ivan; Cerna, Marie; Romzova, Marianna; de Heer, Emile; Baelde, Hans; Bakker, Stephan J.L.; et al. (Diabetes, 2005)
The risk of diabetic nephropathy is partially genetically determined. Diabetic nephropathy is linked to a gene locus on chromosome 18q22.3-q23. We aimed to identify the causative gene on chromosome 18 and to study the mechanism by which the product of this gene could be involved in the development of diabetic nephropathy. DNA polymorphisms were determined in 135 case (diabetic nephropathy) and 107 control (diabetes without nephropathy) subjects. The effect of carnosine on the production of extracellular matrix components and transforming growth factor-β (TGF-β) after exposure to 5 and 25 mmol/l d-glucose was studied in cultured human podocytes and mesangial cells, respectively. A trinucleotide repeat in exon 2 of the CNDP1 gene, coding for a leucine repeat in the leader peptide of the carnosinase-1 precursor, was associated with nephropathy. The shortest allelic form (CNDP1 Mannheim) was more common in the absence of nephropathy (P = 0.0028, odds ratio 2.56 [95% CI 1.36-4.84]) and was associated with lower serum carnosinase levels. Carnosine inhibited the increased production of fibronectin and collagen type VI in podocytes and the increased production of TGF-β in mesangial cells induced by 25 mmol/l glucose. Diabetic patients with the CNDP1 Mannheim variant are less susceptible for nephropathy. Carnosine protects against the adverse effects of high glucose levels on renal cells.
Gesehen am 24.05.2022